Hamlyn history : religion - Farrington, Karen (London : Hamlyn, 1998)
An analysis of every religious belief, from the oldest tribal ceremonies to modern cults. The book covers the origins, practices, rituals and variations which make up each of the world's religions. It aims to put into context belief structures from the earliest times to the present day.
Worship in the ancient world ; Classical paganism ; Judaism ; Hiduism ; Eastern religions ; Bhuddism; Christianity; Islam ; Sikhism ; Modern movements.
Includes index.
Keywords: Religions